Lessons from the failure of the adenovector HIV vaccine. - Blais, M; Rowland-Jones, S (2009)
The much-publicised halting of the joint Merck/HIV Vaccine Trials Network phase IIB candidate HIV-1 vaccine trial in 2007 has led to an unprecedented degree of discussion and introspection amongst the HIV research community. In this commentary, we will summarise the lessons learned from the trial and examine the current state of HIV vaccine research.